Occupational Therapy Holistic Admissions at a Public, Urban Research University: Process, Outcomes, and Transitions. - Stoffel, Ashley; Arias, Dalmina; Van Denend, Toni; Smith, Caitlin; Lee, Jenica; Larson, Maria; Fisher, Gail (Open Journal of Occupational Therapy (OJOT))
Implementing a holistic admissions process reflecting the mission of the university provides the means to expand enrollment of students from diverse backgrounds who have life experiences and values that are well matched to the communities they serve. This article explores the historical significance, outcomes, and transitions of a holistic admissions process in a public, urban research university. The holistic admission process outlined in this article offers a balanced and equitable approach to student selection by considering a broad array of backgrounds, experiences, and attributes beyond traditional metrics, such as grades. With a commitment to inclusivity, access, and belonging, the department developed a rigorous five-stage admissions process that aligned with its mission and values. This process continues to transition in response to trends in the applicant pool, studies of barriers to application and admission, and pertinent state and/or federal laws. A decade-long program evaluation effort at this occupational therapy program examines program outcomes and compares them with national data. The benefits of holistic admissions in occupational therapy education and strategies for the success of holistic and inclusive education are discussed. Future implications for the lasting impact of diversifying the profession are also highlighted.